Cropping and tillage systems effects on soil erosion under climate change in Oklahoma - Zhang XC (Soil Science Society of America Journal, 2012)
Soil erosion under future climate change is very likely to increase because of increases in occurrence of heavy storms. The objective of this study is to quantify the effects of common cropping and tillage systems on soil erosion and surface runoff during 2010 to 2039 in central Oklahoma. A combination of 18 cropping and tillage systems is evaluated using the Water Erosion Prediction project (WEPP) model for 12 climate change scenarios projected by four global climate models (GCMs) under three emissions scenarios. Tillage systems include continuous monocultures of winter wheat, soybean, sorghum, and cotton and double crops of wheat and soybeans. Compared with the present climate, overall t tests show that the future mean precipitation will decrease by some 6;(>98.5;probability), daily precipitation variance increase by 12;(>99;), and mean temperature increase by 1.36d C (<99;). Despite the projected precipitation declines, the overall averaged runoff and soil loss will increase by 19.5 and 43.5;because of increased occurrence of large storms. Soil Erosion is positively related to the degree of tillage disturbances in all cropping systems. Compared with the conventional till, reduced, delayed, and no tillage substantially reduce soil erosion, showing that adoption of conservation tillage will be effective in controlling soil erosion in the next 30 year. cropping systems decrease runoff and soil loss from continuous cotton to soybean to sorghum to wheat in all tillage systems under climate change, indicating a preference of winter wheat for controlling runoff and soil loss in the region.
Keywords: Australia; Canada; Climate generator; Global climate model; Japan; Okalahoma